Замена: ![t=8^{x-1}=8^x/8 t=8^{x-1}=8^x/8](https://tex.z-dn.net/?f=t%3D8%5E%7Bx-1%7D%3D8%5Ex%2F8)
![8\cdot t^2+64t-72<0 8\cdot t^2+64t-72<0](https://tex.z-dn.net/?f=8%5Ccdot+t%5E2%2B64t-72%3C0)
![t^2+8t-9<0 t^2+8t-9<0](https://tex.z-dn.net/?f=t%5E2%2B8t-9%3C0)
![(t+9)(t-1)<0 (t+9)(t-1)<0](https://tex.z-dn.net/?f=%28t%2B9%29%28t-1%29%3C0)
![t\in(-9,1) t\in(-9,1)](https://tex.z-dn.net/?f=t%5Cin%28-9%2C1%29)
![-9<8^x/8<1 -9<8^x/8<1](https://tex.z-dn.net/?f=-9%3C8%5Ex%2F8%3C1)
![8^x<8 8^x<8](https://tex.z-dn.net/?f=8%5Ex%3C8)
![8^x<8^0 8^x<8^0](https://tex.z-dn.net/?f=8%5Ex%3C8%5E0)
![x<0 x<0](https://tex.z-dn.net/?f=x%3C0)
\dfrac{512}{27}" alt="\left(\dfrac{3}{8}\right)^{x+1}>\dfrac{512}{27}" align="absmiddle" class="latex-formula">
\left(\dfrac{3}{8}\right)^{-3}" alt="\left(\dfrac{3}{8}\right)^{x+1}>\left(\dfrac{3}{8}\right)^{-3}" align="absmiddle" class="latex-formula">
![x+1<-3 x+1<-3](https://tex.z-dn.net/?f=x%2B1%3C-3)
![x\in(-\infty,-4) x\in(-\infty,-4)](https://tex.z-dn.net/?f=x%5Cin%28-%5Cinfty%2C-4%29)
![0<9x-1\leqslant9-x^2 0<9x-1\leqslant9-x^2](https://tex.z-dn.net/?f=0%3C9x-1%5Cleqslant9-x%5E2)
1/9\\ 9-x^2\geqslant9x-1 \end{cases} " alt="\begin{cases} x>1/9\\ 9-x^2\geqslant9x-1 \end{cases} " align="absmiddle" class="latex-formula">
1/9\\ x^2+9x-10\leqslant0 \end{cases}" alt="\begin{cases} x>1/9\\ x^2+9x-10\leqslant0 \end{cases}" align="absmiddle" class="latex-formula">
1/9\\ x\in[-10,1] \end{cases}" alt="\begin{cases} x>1/9\\ x\in[-10,1] \end{cases}" align="absmiddle" class="latex-formula">
Ответ: ![x\in(1/9,1] x\in(1/9,1]](https://tex.z-dn.net/?f=x%5Cin%281%2F9%2C1%5D)